Kosmopolitanisme Hukum Islam: Peredaran Kitab Minhāj al-ṭālibīn di Nusantara - Masudi, Idris (Studia Islamika, 2022)
Mahmood Kooria. 2022. Islamic law in Circulation: Shāfiʿī Texts across the Indian Ocean and the Mediterranean. Cambridge: Cambridge University Press.Mahmood Kooria’s Islamic Law in Circulation examines the development of postclassical Islamic law pertaining to Shafi’ism in the eastern Mediterranean and the Indian Ocean. Using the nodal point of Minhāj al-ṭālibīn, authored by 13th-century Damascene jurist Yaḥyā bin Sharaf al-Nawawī, this book circumnavigates the major narratives of Shāfiʿī legal circulation over a millennium. Based on this Mamluk-era text, Kooria traces the formation of the legal oceanic community by elucidating its enormous intertextual and intellectual networks and ramifications. The main argument of Kooria’s book is that historical Shāfiʿīsm in the postclassical Islamic communities took place not by center-periphery coercion or state conquest, but through cross-cultural negotiations between scholars and itinerant traders in maritime milieux throughout Africa, Arabia, and Asia.